2012
DOI: 10.1109/tmag.2012.2209122
|View full text |Cite
|
Sign up to set email alerts
|

Switching Distributions for Perpendicular Spin-Torque Devices Within the Macrospin Approximation

Abstract: We model "soft" error rates for writing (WSER) and for reading (RSER) for perpendicular spintorque memory devices by solving the Fokker-Planck equation for the probability distribution of the angle that the free layer magnetization makes with the normal to the plane of the film. We obtain: (1) an exact, closed form, analytical expression for the zero-temperature switching time as a function of initial angle; (2) an approximate analytical expression for the exponential decay of the WSER as a function of the tim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
120
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(125 citation statements)
references
References 50 publications
5
120
0
Order By: Relevance
“…During the last decade, various analytical and numerical approaches to the calculation of the measurable parameters of STT devices such as the magnetization reversal time, etc. via the magnetic Langevin and/or Fokker-Planck equations including STT have been developed [130,137,[140][141][142][143][144][145][146][147][148][149][150]. These approaches mainly generalize methods originally developed for treating thermal fluctuations in nanoscale ferromagnets at zero STT, such Fig.…”
Section: E Smentioning
confidence: 99%
“…During the last decade, various analytical and numerical approaches to the calculation of the measurable parameters of STT devices such as the magnetization reversal time, etc. via the magnetic Langevin and/or Fokker-Planck equations including STT have been developed [130,137,[140][141][142][143][144][145][146][147][148][149][150]. These approaches mainly generalize methods originally developed for treating thermal fluctuations in nanoscale ferromagnets at zero STT, such Fig.…”
Section: E Smentioning
confidence: 99%
“…For I Ic 0 , the value of the exponent is approximately 1, in agreement with Li and Koch, and increases up to approximately 2.2 with increasing current. For the case of out-of-plane anisotropy, Butler et al 12 solved the Fokker-Planck equation for the switching distribution and reported that the exponent should be n = 2. Pinna et al 13 reported that, in a system with uniaxial anisotropy, n = 2 is a much better fit to the data at long time scales than n = 1, and the crossover regime between deterministic and thermal effects could span very large switching timescales.…”
Section: Resultsmentioning
confidence: 99%
“…The results of this simple model appear in reasonable agreement, with a full Fokker-Planck result generating slightly faster switching times at the low overdrive I=I c $ 1 ð Þlimit. The exponentially decreasing tail of the non-switching probability E r , either in t or in I, remains essentially the same [69,75,77]. This tail, however, is yet to be experimentally observed, probably due to the non-macrospin nature of the devices experimentally studied to date [78,79].…”
Section: Super-threshold Spin Torque and Switching Speedmentioning
confidence: 94%
“…This tail, however, is yet to be experimentally observed, probably due to the non-macrospin nature of the devices experimentally studied to date [78,79]. Higher-precision statistics at shorter switching time (well below 10ns) and for smaller junctions (probably below 20 nm) would bring experimental situation closer to the macrospin model assumptions, and one would have a better understanding of whether this macrospin model predicted "stagnation" behavior [69,75,77] and is likely to cause practical problems for reliable write operation for a memory element in its small-size limit, for example.…”
Section: Super-threshold Spin Torque and Switching Speedmentioning
confidence: 97%